Implementation of the Think Pair Share Cooperative Learning Model to Improve Students' Understanding of Islamic Religious Education at SMP Negeri 1 Airgegas - Julia, Julia; Noor, Wahyudin; Rudini, Rudini (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study aims to examine the implementation of the Think Pair Share type of Cooperative Learning model and its impact on improving students' understanding in Islamic Religious Education at SMP Negeri 1 Airgegas. The background of this research is the low level of students’ comprehension of Islamic Religious Education material, which is attributed to the use of monotonous and passive teaching methods. The research employs a quantitative approach, involving two sample classes: an experimental class applying the Think Pair Share model and a control class using conventional teaching methods. The implementation of the TPS model in the experimental class was carried out through three stages: think (individual reflection), pair (discussion in pairs), and share (sharing discussion results with the class). The research instruments used were pre-tests and post-tests to measure students' understanding before and after the treatment. The Wilcoxon test results for the experimental group showed a significant improvement between pre-test and post-test scores, indicating that the TPS model effectively enhanced students’ comprehension. Furthermore, the Mann-Whitney test showed a significant difference between the post-test scores of the experimental and control groups, suggesting that students taught using the TPS model achieved a higher level of understanding compared to those taught with conventional methods